Carvedilol and its combination with digoxin for heart rate control in patients with persistent atrial fibrillation and chronic heart failure - S. N. Tereshchenko (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To compare effectiveness of carvedilol as monotherapy and in combination with digoxin for heart rate (HR) control in patients with persistent atrial fibrillation (AF) and chronic heart failure (CHF). Material and methods. In total, 45 men and women, aged 42-77 years, with persistent AF and NYHA Functional Class II-III CHF were randomized into two treatment groups, and sub-divided by baseline ejection fraction, EF (EF>45%; EF<45%) and HR (HRMOO; HR<100 bpm). Clinical and hemodynamic parameters, as well as beta-adrenoreactivity were assessed during the study. Results. The most manifested clinical signs of myocardial contractility improvement were observed in combined therapy group. At the same time, in patients with EF>45%, non-significant benefits of carvedilol monotherapy were registered. Conclusion. In CFH patients with persistent AF and baseline EF>45%, carvedilol monotherapy was more effective; in EF>45%, combined therapy had more clinical benefits. Moreover, combined therapy was more effective in baseline HRMOO, and carvedilol monotherapy - in baseline HR<100.